2006
DOI: 10.1038/sj.jhh.1002097
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial vascular tone during the night in patients with essential hypertension

Abstract: The time-dependent incidence of cardiovascular events points to an important role of chronobiology for arterial properties. To evaluate arterial properties in patients with essential hypertension, we assessed arterial vascular tone during sleep at night in patients with essential hypertension and normotensive control subjects. Vascular tone was continuously quantified by the reflective index obtained by non-invasive digital photoplethysmography and an algorithm for continuous, investigatorindependent, automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
(43 reference statements)
3
12
0
1
Order By: Relevance
“…In these studies, sympathetic activity was derived from measurements of muscle sympathetic nerve activity. Previous experimental studies from our group already indicated that an elevated sympathetic nerve activity measured by microneurography from the peroneal nerve results in an increased reflective index [18]. In the present study, we confirmed that apnoea increased the reflective index in a similar way to vasoconstriction induced by the cold-pressure test.…”
Section: Sleep-related Disorders a Scholze Et Alsupporting
confidence: 80%
See 2 more Smart Citations
“…In these studies, sympathetic activity was derived from measurements of muscle sympathetic nerve activity. Previous experimental studies from our group already indicated that an elevated sympathetic nerve activity measured by microneurography from the peroneal nerve results in an increased reflective index [18]. In the present study, we confirmed that apnoea increased the reflective index in a similar way to vasoconstriction induced by the cold-pressure test.…”
Section: Sleep-related Disorders a Scholze Et Alsupporting
confidence: 80%
“…This area covers the diastolic shoulder region to the dicrotic wave, which is in part formed by pulse waves reflected back from peripheral vascular sites of impedance mismatch. As indicated in our previous studies, short-term changes of the reflective index reflect vasoconstriction or vasodilatation [18,19]. Earlier studies from our group indicated that the reflective index shows a significant positive correlation with invasively determined systemic vascular resistance by pulmonary artery catheter (Spearman correlation, r50.64, p,0.01, n520).…”
Section: Digital Photoplethysmographymentioning
confidence: 78%
See 1 more Smart Citation
“…41 RI at rest reflects the current state of arterial tone, 16,17 and a lower RI is an indicator of more relaxed arteries. Also FST reflects blood flow 42, 43 and is regulated by sympathetic tone, 44 which relates FST to RI and endothelial function, 45 but not to SI. 16,17 Thus, a higher FST is also a marker of more open peripheral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic arterial vascular tone is increased in patients with essential hypertension during the night compared with normotensive control subjects. This increased vascular tone might contribute to the well-known changes of arterial structure in essential hypertension and eventually lead to cardiovascular disease (22).…”
Section: Diabetes-associated Risk Factors For Arterial Hypertensionmentioning
confidence: 99%